Unveiling massive numbers of cancer-related urinary-microRNA candidates via nanowires - Takao Yasui; Takeshi Yanagida; Satoru Ito; Yuki Konakade; Daiki Takeshita; Tsuyoshi Naganawa; Kazuki Nagashima; Taisuke Shimada; Noritada Kaji; Yuta Nakamura; Ivan Adiyasa Thiodorus; Yong He; et al. (My University, 2017)
We demonstrate the first reported methodology using nanowires that unveils massive numbers of cancer-related urinary microRNAs.
Keywords: Extracellular vesicles in disease